Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{1\cdot2}+\frac{1}{2\cdot3}+\frac{1}{3\cdot4}+.....+\frac{1}{59\cdot60}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+.....+\frac{1}{59}-\frac{1}{60}\)
\(=1-\frac{1}{60}\)
\(=\frac{59}{60}\)
1/3x + 3/4x - 75% = -5 1/4
=> x - 3/4 = -21/4
=> x = -21/4 + 3/4
=> x = -9/2
60%x + 5/6x = -76
=> 3/5x + 5/6x = -76
=> 43/30x = -76
=> x = -76 : 43/30
=> x = -2280/43
\(\frac{1}{3}x+\frac{3}{4}x-75\%=-5\frac{1}{4}\)
\(\frac{13}{12}x-\frac{3}{4}=-\frac{21}{4}\)
\(\frac{13}{12}x=-\frac{9}{2}\)
\(x=-\frac{54}{13}\)
\(60\%.x+\frac{2}{3}x=-76\)
\(\frac{3}{5}x+\frac{2}{3}x=-76\)
\(\frac{19}{15}x=-76\)
\(x=-60\)
a) 2.(x+1) - 3 = 11
2.(x+1) = 14
x + 1 = 7
x = 6
b) 60 - 5.(x-3) = 50
5.(x-3) = 10
x-3 = 2
x = 5
c) (10+2x).43 = 45
10 + 2x = 16
2x = 6
x =3
\(a,2\cdot\left(x+1\right)-3\left(11\right)=0.\)
\(\left(2\cdot\left(x+1\right)-3\right)-11=0.\)
\(2x-12=2\cdot\left(x-6\right)\)
\(2\cdot\left(x-6\right)=0.\)
\(x-6=0.\)
\(x=6.\)
\(b,\left(60-5\cdot\left(x-3\right)\right)-50=0\)
\(25-5x=-5\cdot\left(x-5\right)\)
\(-5x\left(x-5\right)=0.\)
\(x-5=0\)
\(x=5\)
Câu c khó quá bn tự làm nhé.
học tốt
a ) x = 2
b ) x = 7
c ) x = 5
d ) đề sai ......! hoặc x = rỗng .
e ) x = 5
(x + 1)³ - 4 = 60
(x + 1)³ = 60 + 4
(x + 1)³ = 64
(x + 1)³ = 4³
x + 1 = 4
x = 4 - 1
x = 3